STAPES CERRAHİSİNDE UZUN DÖNEM İŞİTME SONUÇLARI - BOZAN, Serdar; ÖZTÜRK, Özcan; YÜKSEL, Sancak; KARAMAN, Emin; YILMAZ, Süleyman; ENVER, Özgün (Cerrahpaşa Medical Journal, 2019)
Background and Design.- We investigate the long-term clinical results of otosclerotic patients after stapes surgery. Retrospectively we investigate the odiogram of 17 female, 8 male totally 25 patients’ 26 ears. Closure success of the air bone gap was statistically evaluated with Wilcoxon test. Results.- The age of the patients were between 20-48 (mean age 36.2±8.0) and their follow up time were 24 -75 months (meanly 45.0±15.8). The air bone gap before the surgery were 15-48 dB (mean: 31.9±9.5). Under general anesthesia stapedotomy were done to 24 ears and stapedectomy were done to 2 ears. After follow up period the postoperative air bone gap were 0-38 dB (mean: 15.8±12.1). The difference between the pre- and postoperative air-bone gaps were statistically significant (p=0.000). In one patient neurosensorial hearing loss appeared. Conclusion.- Over the long term, effective and good results can be get with otosclerotic patients after stapes surgery.